A candidate chromosome inversion in Arctic charr (Salvelinus alpinus) identified by population genetic analysis techniques. Issue 10 (28th July 2021) - Hale, Matthew C; Campbell, Matthew A; McKinney, Garrett J
Abstract: The "genomics era" has allowed questions to be asked about genome organization and genome architecture of non-model species at a rate not previously seen. Analyses of these genome-wide datasets have documented many examples of novel structural variants (SVs) such as chromosomal inversions, copy number variants, and chromosomal translocations, many of which have been linked to adaptation. The salmonids are a taxonomic group with abundant genome-wide datasets due to their importance in aquaculture and fisheries. However, the number of documented SVs in salmonids is surprisingly low and is most likely due to removing loci in high linkage disequilibrium when analyzing structure and gene flow. Here we re-analyze RAD-seq data from several populations of Arctic charr ( Salvelinus alpinus ) and document a novel ∼1.2 MB SV at the distal end of LG12. This variant contains 15 protein-coding genes connected to a wide-range of functions including cell adhesion and signal transduction. Interestingly, we studied the frequency of this polymorphism in four disjointed populations of charr—one each from Nunavut, Newfoundland, Eastern Russia, and Scotland—and found evidence of the variant only in Nunavut, Canada, suggesting the polymorphism is novel and recently evolved.